Syntactic cues to the noun and verb distinction in Mandarin child-directed speech. Issue 4 (August 2019) - Ma, Weiyi; Zhou, Peng; Golinkoff, Roberta Michnick; Lee, Joanne; Hirsh-Pasek, Kathy
The syntactic structure of sentences in which a new word appears may provide listeners with cues to that new word's form class. In English, for example, a noun tends to follow a determiner ( a / an / the ), while a verb precedes the morphological inflection [ing]. The presence of these markers may assist children in identifying a word's form class and thus glean some information about its meaning. This study examined whether Mandarin, a language that has a relatively impoverished morphosyntactic system, offers reliable morphosyntactic cues to the noun–verb distinction in child-directed speech (CDS). Using the CHILDES Beijing corpora, Study 1 found that Mandarin CDS has reliable morphosyntactic markers to the noun–verb distinction. Study 2 examined the relationship between mothers' use of a set of early-acquired nouns and verbs in the Beijing corpora and the age of acquisition (AoA) of these words. Results showed that the occurrence of the form class markers is a reliable predictor of the AoA for the early-acquired nouns and verbs.